MANAJEMEN PEMELIHARAAN SARANA PRASARANA PENDIDIKAN - Andri Cahyo Purnomo (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to determine the management of the maintenance of educational infrastructure in schools. This research is a qualitative type through literature study, namely research that is carried out only based on written works, including research results, both published and unpublished. The results of this research literature review show that facilities and infrastructure will experience a drastic decline if maintenance efforts are not carried out properly and optimally, so that the maintenance of educational facilities and infrastructure needs to be managed properly. The purpose of maintaining facilities and infrastructure, namely a) to optimize the service life of the equipment; b) to ensure the operational readiness of the equipment; c) to ensure the availability of the necessary equipment; d) to ensure the safety of people or students who use the tool. Various kinds of maintenance of educational facilities and infrastructure, namely a) routine/periodic maintenance; b) emergency maintenance; c) preventive maintenance.